Relationship of Wheat Yield with Agroclimatic Indices under Varying Thermal Regimes, Nitrogen Levels and Stress Management Strategies - Kaur, Sukhjeet; Singh, Som Pal; Kingra, P. K. (International Journal of Bio-resource and Stress Management, 2023)
The field experiments were carried out during rabi seasons of 2013−14 and 2014−15 at Research Farm, School of Climate Change and Agricultural Meteorology, PAU, Ludhiana to study the effect of different temperature regimes, nitrogen levels and post anthesis strategies on phenology growth, development and grain yield of wheat. The experiment was laid out in Split-Split plot design having three temperature regimes (D1=October 30, D2=November 15 and D3= November 30) in main plot, three nitrogen levels (N1=RDF (Recommended dose of N), N2=125% RDF (25% more than recommended N), N3=150% RDF (50% more than recommended N) in sub plot and four heat stress management post-anthesis strategies (P0=Control, P1=Water sprayed, P2=Foliar spray of ZnSO4.7H20(0.5%), P3=Thiourea (10 mM) at anthesis and 20 days after anthesis in sub-sub plot during both years. The agrometeorological indices such as accumulated growing Degree Days (AGDD), heliothermal units (HTU), photo thermal units (PTU) and heat use efficiency (HUE) were calculated and their relation with grain yield was also observed. The results showed that the crop sown on October 30 with 150% RDF when spray at or after anthesis at regular intervals with any of stress alleviating chemicals such as ZnSO4.7H2O (0.5%), Thiourea (10 mM) or water accumulated more number of growing degree days, photo thermal units and had higher heat use efficiency than other treatments because crop exhibited best growth and development as the favorable environmental conditions concided with higher heat unit requirement of different phenophases and gave higher grain yield